2022
DOI: 10.1163/22941932-bja10092
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drought stress on the formation and lignification of eucalyptus wood cells

Abstract: Summary Environmental adaptation and cell differentiation processes are factors that influence the anatomical elements of wood. The objective of this study was to investigate the effect of water deficit on lignin composition in anatomical elements and on the characteristics of vessel-neighboring cells. Six-year-old clones of Eucalyptus urophylla and Eucalyptus grandis × Eucalyptus camaldulensis from wet and dry regions were used. All regions received a rainfall exclusion treatment. Cell wall width, cell wall t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Wide tree‐ring sectors including APF cell types at different relative distances to vessels, including both surrounding and distant cells, were delimited to minimize the impacts of vessel proximity on APF timing calculations (Fig. 3a; Čufar et al ., 2008; Moulin et al ., 2022). The total number of vessel‐surrounding cells measured was consequently lower than that of the distant cells.…”
Section: Methodsmentioning
confidence: 99%
“…Wide tree‐ring sectors including APF cell types at different relative distances to vessels, including both surrounding and distant cells, were delimited to minimize the impacts of vessel proximity on APF timing calculations (Fig. 3a; Čufar et al ., 2008; Moulin et al ., 2022). The total number of vessel‐surrounding cells measured was consequently lower than that of the distant cells.…”
Section: Methodsmentioning
confidence: 99%
“…Together these findings suggest that the ability of plants to combat oxidative stress, and therefore drought, significantly depends on their capacity to modulate the synthesis of phenols. In addition, E. urophylla grown under water deficit increased its concentrations of wall-bound phenolics, as a strategy for increasing water transport and improving the use of water resources [58]. Thus, it has been reported that phenolics such as salicylic acid regulate aquaporins for increasing the hydraulic properties of roots in arbuscular mycorrhizal maize plants subjected to drought [59].…”
Section: Droughtmentioning
confidence: 99%
“…During dry periods, the decrease of δ 2 H on wood compounds in pine plantations may alter cell wall integrity and synthesis making these trees more vulnerable to xylem embolism. Trees from natural forests could be more adapted to low precipitation during the growing season by increasing the activity of cellulosic compounds, retaining higher turgor levels during cell enlargement at low water potentials thus forming more tracheids with thicker cell walls [73].…”
Section: Improved Growth Resilience In Natural Forestsmentioning
confidence: 99%